Identification of Slightly Halophilic Bacteria From Salted Sheepskin Samples and Investigation of Their Biotechnological Importance - ÇAĞLAYAN, PINAR (My University, 2024)
In the leather industry, skins/hides are salted immediately after the animal is slaughtered to prevent the enzymatic activities of bacteria. Although the salt-curing method prevents the growth of mesophilic bacteria, halophilic bacteria can develop in skins/hides that are stored for a long time, causing a decrease in leather quality. In the literature, it has been stated that slightly halophilic bacteria are isolated from products with a certain concentration of salt content. Since there is no study on the presence of these bacteria in salted raw hides, slightly halophilic bacteria were isolated and molecularly identified from ten sheepskin samples which were stored at 20°C for 6 months in our study. Also their biotechnologically important enzymes were evaluated, their bacteriocin production capacity was determined and the antibacterial efficacy of a chemical (sodium dimethyldithiocarbamate) used in the leather industry at certain concentrations were tested against these isolates. The total number of slightly halophilic bacteria, the total number of proteolytic slightly halophilic bacteria and the total number of lipolytic slightly halophilic bacteria in skin samples were determined as 1 x 104 – 4 x 105CFU/g, 2 x 103 – 4 x 104CFU/g and 1 x 102 – 3 x 104CFU/g, respectively. A total of 20 slightly halophilic bacteria were isolated from skin samples. Gram-positive and rod-shaped isolates showed optimum growth at 3-5% salt, 37°C-45°C and pH7-8. Protease, lipase, DNase, pullulanase, xylanase and cellulase produced by 100%, 61%, 83%, 11%, 44%, 88% isolates, respectively. In addition, oxidase and catalase activities were detected in all isolates. It has been determined that the isolates were able to produce acids from different sugar sources (D-xylose, D-mannose, D-ribose, sucrose) and can use amino acids (L-cysteine, L-glycine, L-alanine, L-threonine) found in the skin’s structure. According to the 16S rRNA sequence analysis results, the isolates belonged to the Bacillus genus (B. rugosus, B. amyloliquefaciens, B. haynesii, B. aerius, B. safensis, B. pumilus, B. kochii, B. mojavensis and B. atrophaeus). Among all isolates producing bacteriocin, the bacteriocin produced by Bacillus aerius had a thermostable structure, did not lose its activity at high pH and salt values, completely inactivated its activity when treated with proteinase K enzyme, and had its antibacterial activity when treated with lipase enzyme. Therefore, considering that some species are resistant to antimicrobials, purified bacteriocins can be used as a preservative in the leather industry. The isolates were sensitive to tested chemical substance at a certain concentrations (4000, 2000, 1000, 500, 250, 125, 62.5, 31.2, 15.6, 7.8μg/mL) and minimum inhibitory concentration (MIC) were detected. The MIC values of the isolates were determined as as 62.5μg/mL (B. rugosus), 31.2μg/mL (B. haynesii, B. safensis, B. mojavensis) 15.6μg/mL (B. amyloliquefaciens, B. aerius, B. kochii) 7.8μg/mL (B. pumilus) and 3.9μg/mL (B. atrophaeus). In this way, unnecessary use of chemicals in the soaking process will be prevented.
Keywords: Kimya Mühendisliği ve Teknolojisi; Kimya; Temel Bilimler; Mühendislik ve Teknoloji; Chemical Engineering and Technology; Chemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Malzeme Bilimi; MÜHENDİSLİK, KİMYASAL; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; MATERIALS SCIENCE; CHEMISTRY; ENGINEERING, CHEMICAL; Genel Kimya; Fizik Bilimleri; Genel Kimya Mühendisliği; Genel Malzeme Bilimi; General Chemistry; Physical Sciences; General Chemical Engineering; General Materials Science